Using Soft Robotic Technology to Fabricate a Proof‐of‐Concept Transcatheter Tricuspid Valve Replacement (TTVR) Device. Issue 4 (27th February 2019) - Amiri Moghadam, Amir Ali; Jang, Sun‐Joo; Caprio, Alexandre; Liu, Jun; Singh, Harsimran S.; Min, James K.; Dunham, Simon; Mosadegh, Bobak
Abstract: Soft robotic technology has great potential for advancing the performance of transcatheter cardiac devices, due to its inherent properties for conformability and simple actuation. This work provides a proof‐of‐concept tricuspid valve that can be delivered via a catheter and made with soft balloons in order to avoid critical anatomical features in the tricuspid valve and to enhance anchoring. This soft valve is inflatable and thus can be repositioned during delivery to conform and anchor well to the native anatomy. Using a 3D printed model of the tricuspid valve, which is segmented from a patient CT scan, the anchoring force, functionality of the valve, and prevention of paravalvular leakage are demonstrated. Abstract : Soft robotic technology is used to fabricate a conformable prosthetic valve for transcatheter tricuspid valve replacement. The prosthetic valve comprises three inflatable features: a soft stent that holds the three leaflets of the valve, a sealing balloon that prevents paravalvular leakage, and an anchoring balloon that keeps the valve in the right ventricle.